Clinical outcomes of double-screw fixation with bone grafting for displaced scaphoid nonunions: A series of 21 cases - Ma, Wei; Yao, Jeffrey; Guo, Yang (Frontiers in Surgery, 2023)
Purpose: This study reports the clinical outcome of double screws fixation with bone grafting for displaced scaphoid nonunion. Patients and Method: This study was a retrospective survey.From Jan 2018 to Dec 2019, 21 patients with displaced scaphoid fracture underwent open debridement and two headless compression screws fixation with bone grafting. Preoperative and postoperative lateral intrascaphoid angle (LISA) and scapholunate angle (SLA) were recorded. Grip strength(% of the healthy side), active range of motion (AROM), visual analogue scale(VAS) and patient- rated wrist evaluation (PRWE) scores for preoperative and postoperative at final follow-up were obtained for all patients to compare. Results: Patients were treated an average 38.3 months(range 12-250) after the injury. The average time of postoperative follow-up was 30.5 months(range 24-48). All fractures were achieved union at a mean of 2.7 months (range 2-4) after surgery and 14 scaphoids of 21 patients (66.7%) healed by 8 weeks. CT scans showed no evidence of cortical penetration of either screw in all patients. There was statistically significant improvement in AROM, grip strength and PRWE. No complications occurred in this study, and all of the patients returned to work. Conclusion: This study indicate that double screws fixation with bone grafting is a effective technique for treatment of displaced scaphoid nonunion.